Preparedness of Ob/Gyn residents for fellowship training in gynecologic oncology - David W. Doo; Matthew Powell; Akiva Novetsky; Jeanelle Sheeder; Saketh R. Guntupalli (Elsevier, 2015)
Residency training in obstetrics and gynecology is being challenged by increasingly stringent regulations and decreased operative experience. We sought to determine the perception of preparedness of incoming gynecologic oncology fellows for advanced surgical training in gynecologic oncology. An online survey was sent to gynecologic oncologists involved in fellowship training in the United States. They were asked to evaluate their most recent incoming clinical fellows in the domains of professionalism, level of independence/graduated responsibility, psychomotor ability, clinical evaluation and management, and academia and scholarship using a standard Likert-style scale. The response rate among attending physicians was 40% (n = 105/260) and 61% (n = 28/46) for program directors. Of those who participated, 49% reported that their incoming fellows could not independently perform a hysterectomy, 59% reported that they could not independently perform 30 min of a major procedure, 40% reported that they could not control bleeding, 40% reported that they could not recognize anatomy and tissue planes, and 58% reported that they could not dissect tissue planes. Fellows lacked an understanding of pathophysiology, treatment recommendations, and the ability to identify and treat critically ill patients. In the academic domain, respondents agreed that fellows were deficient in the areas of protocol design (54%), statistical analysis (54%), and manuscript writing (65%). These results suggest that general Ob/Gyn residency is ineffective in preparing fellows for advanced training in gynecologic oncology and should prompt a revision of the goals and objectives of resident education to correct these deficiencies.